Forensic geotechnical investigation of cracks in buildings around Gubi and environs, Bauchi, Northeast Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2026)
The study aims to undertake a geoforensic investigation of the major causes of cracks in buildings in Gubi and its environs. To achieve this, geophysical and geotechnical approaches were adopted to characterize the soil properties and subsurface rocks. Five vertical electrical soundings (VES) were purposively carried out using Schlumberger’s configuration to characterize the geoelectrical properties of the soil. In addition, 10 disturbed soil samples were collected for geotechnical laboratory analyses. The indices analyzed are natural moisture content (NMC), particle size distribution, Atterberg limits, free swell index, linear shrinkage, and specific gravity. Three geoelectrical layers comprising topsoil, weathered layer, and bedrock basement were delineated within the study area. The resistivity values (10.8–42.8 Ωm) suggest that the top and weathered layers of VES 1 and VES 2 are incompetent clay material. The results of the geotechnical tests, however, revealed that the site is underlain by poorly graded clay sand to sand clays with low to medium plasticity, specific gravity (2.2–2.7), liquid limit (25.8%–39.0%), plastic limit (18.8%–35.1%), NMC (7.10%–25.0%), and linear shrinkage limit (2.8%–11.3%). The result generally shows that the soils in the northeastern parts have NMC, linear shrinkage, and free swell value above the permissible limit for a foundation. It was concluded that the differential settlement of the incompetent subsoil material is responsible for the failure of the foundation material and building walls.